1111. #BeASteward: Transforming Infectious Diseases Fellows Into Antimicrobial Stewards Using the IDSA Antimicrobial Stewardship Curriculum. (31st December 2020) - Luther, Vera; Shnekendorf, Rachel A; Jennifer, Spicer O; Logan, Ashleigh; Barsoumian, Alice; Schwartz, Brian; Bryson-Cahn, Chloe; Ohl, Christopher; Ohl, Christopher; Beeler, Cole; MacDougall, Conan; Stack, Conor; et al.
Abstract: Background: The Infectious Diseases Society of America (IDSA) has supported the development of the Core and Advanced Antimicrobial Stewardship (AS) Curricula for fellows to ensure the future ID workforce is effectively prepared to practice, participate in and lead AS efforts in health care institutions. The Core AS Curriculum is currently available; the Advanced AS Curriculum pilot will begin July, 2020. Methods: IDSA formed the AS Curriculum Workgroup, comprised of leaders in AS and medical education from institutions across the country, to lead the AS Curricula development process. The workgroup conducted two surveys of ID Fellowship Program Directors, one in 2016 for the core curriculum and a second in 2018 for the advanced curriculum, to assess existing AS educational resources and determine needs for additional AS educational and evaluation resources. The workgroup used the evaluation data to inform the content, delivery methods, and assessment tools for the curricula. The Core AS Curriculum is designed to provide fellows foundational knowledge and skills in AS. The Advanced AS Curriculum is designed to provide fellows the knowledge and skills to become leaders in AS. The Core AS Curriculum was piloted by 56 ID Fellowship Programs in 2018 and then made broadly available via IDSA Academy in 2019. Pilot data will be used to improve future iterations of the curriculum. The Advanced AS Curriculum pilot will begin in 2020 and will be broadly available in 2021. Results: The curricular packages contain a variety of training resources including eLearning modules, lectures slides, case-based questions, videos, reading materials, pocket cards, group-based learning, role play exercises and simulations. The modules can be taught by faculty to fellows or conducted as a self-directed learning experience. Program directors and fellows who participated in the Core AS Curriculum pilot reported that their fellowship program was significantly more effective in teaching multiple key stewardship content areas (Table). Table. Conclusion: Evaluation data from programs who piloted the Core AS Curriculum indicate that this blended learning experience is an effective method for teaching AS and in providing educational and assessment tools for ID fellowship programs. The Advanced AS Curriculum will be similarly evaluated. Disclosures: Julie Ann Justo, PharmD, MS, BCPS-AQ ID, bioMerieux (Speaker's Bureau)TRC Healthcare (Speaker's Bureau)